Effect of Maternal Exercise on Diet-induced Redox Imbalance in Hippocampus of Adult Offspring. (15th June 2020) - August, P.M.; Hözer, Régis; Rodrigues, K.S.; dos Santos, B.G.; Maurmann, R.M.; Scortegagna, M.C.; Matté, Cristiane
Highlights: Maternal swimming exercise without overload could prevent an increase in offspring glycemia caused by a high-fat diet. Maternal exercise with or without overload can improve the offspring' hippocampal antioxidant defenses. Maternal exercise without overload could prevent the diet-induced superoxide increase in the offspring hippocampus. Abstract: Physical exercise practice has been increasingly recommended in the prevention and treatment of chronic diseases, causing a positive effect from body weight/fat loss to improved cognitive function. Maternal exercise seems to induce the same positive lifelong adaptations to the offspring. We hypothesized that maternal exercise can prevent redox imbalance in adult offspring's hippocampus exposed to a high-fat diet (HFD). Female Wistar rats were divided into three groups before and during pregnancy: (1) sedentary, (2) swimming exercise, and (3) swimming exercise with overload. On 60 days of age, the male pups were divided into standard diet or HFD for one month, yielding normal and HFD subgroups for each maternal condition. Maternal interventions did not alter gestational parameters, birth outcomes, and offspring weight gain from weaning to 90 days of age. The HFD consumption increased body fat, which was not prevented by maternal exercise. Serum glucose levels were increased by HFD, an effect that was prevented by unload maternal exercise. In the hippocampus, both maternal exercise intensities could increase antioxidant defense. Hippocampal redox homeostasis was impaired by HFD, causing increased superoxide levels, which was prevented by exercise without load, while overload caused only a reduction of the effect. In summary, the practice of swimming exercise without overload during pregnancy seems to be more beneficial when evaluated in animal model, preventing HFD induced redox imbalance and increasing antioxidant defense while overload swimming exercise during pregnancy demonstrated a negative effect on offspring submitted to HFD consumption.